Does Body Image Affect Quality of Life?: A Population Based Study - Nayir, Tufan; Uskun, Ersin; Yürekli, Mustafa Volkan; Devran, Hacer; Çelik, Ayşe; Okyay, Ramazan Azim (PLOS ONE, 2016)
Body image (BI) can be described as the assessment of both positive and negative emotion for one’s own body parts and their characteristics by himself or herself. Current research has concentrated mostly on the status of negative BI as a risk factor for mental health problems rather than as a public health problem, thereby little is known about the effects of BI on quality of life. Thus, the purpose of this study was to assess the BI and Quality of Life (QoL) of individuals and to investigate the relationship between the two. Individuals over 15 living in Isparta city center constitute the universe of this cross-sectional analytical study, carried out in 2014. The BI of individuals was measured by the Body Image Scale and The QoL of individuals was measured using the World Health Organization (WHO) Quality of Life Scale Short Form. The mean age of the participants was 31.9 ± 13.0 and 56.0% were female, 36.8% were married and 81.7% had education above high school. 25.7% had at least one chronic disease and 17.7% received medication regularly. Having good-very good health perception, having higher income than expenses, making regular exercises were predictors in enhancing the quality of life in certain aspects, however having a good body image came out as a predictor enhancing the quality of life in all sub-domains. BI was found closely related with QoL in all sub-domains. Our findings suggest that greater attention should be to be given to BI as a strong predictor of QoL.